Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Optimized straw–nitrogen management enhances crop yield, soil carbon sequestration, and economic returns in dryland maize systems of Northwest China - Yunfei Ren; Jiayi Li; Fu Liu; Longchuang Zhang; Xiu Chen; Haibo Hu; Xiaoyu Ning; Yeye Zhang; Jinxia Wang; Xiaozhou Li; Shuangguo Zhu; Fei Mo (Soil and Tillage Research, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Design of dual-function soil amendment via co-roasting K-feldspar with soda residue and oyster shell for acidity amelioration and potassium supply - Ernest Uwiringiyimana; Ren-Yong Shi; Jiu-Yu Li; Jia-Ning Gao; Yong-Ming Fu; Md. Romel Biswash; Cong-Ming Wu; Ren-Kou Xu (Journal of Environmental Chemical Engineering, 2026)

Two-pronged strategy of pore size sieving and recognition sites tailoring for perfluoropropylene-perfluoropropane separation - Zongzhen Han; Meiting Wang; Meng Gao; Kunhua Wang; Hao Yu; Zhiguo Bian; Ruitao Lv; Wei Chen; Liangmin Ning; Min Fu (Chemical Engineering Journal, 2026)

Nanoscale interfacial scaffold enables perovskite/silicon tandems with 34% efficiency and an open-circuit voltage over 2.01 V - Huimin Zhang; Qingshui Zheng; Hongbo Mo; Fu Zhang; Zhijie Rao; Linyu Ning; Yue Yin; Dongsheng Yang; Zheng Fang; Lei Ding; Yongcai He; Xixiang Xu; et al. (Science Bulletin, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Toppling failure mechanism of anti-dip rock slopes under hydrodynamic actions: Insights from centrifuge model tests and numerical simulations - Yang Wang; Fei Ye; Ning Sun; Yinxiang Cui; Qiang Chen; Wenxi Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Antifungal effects and the underlying mechanisms of combined sulfur dioxide fumigation and hypobaric treatment against pathogenic fungi and its application in dried apricots - Yujie Liu; Yuyao Yuan; Tooba Mumtaz; Bin Wu; Ning Wang; Yinghua Fu (Food Control, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Synergistic regulation of bimetallic d-band centers in NiM-NiMOx (M = Co/Cu) catalysts toward enhancing selective hydrogenation - Liangmin Ning; Jun Xie; Shiyan Sheng; Jiawen Wang; Tianyu Zhang; Shuai Li; Shuanglu Fu; Tianqi Xie; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Novel Hepatopancreas-Predominant C-Type Lectin (LvCTL) Contributes to Resistance Against Vibrio parahaemolyticus in Shrimp Litopenaeus vannamei - Ning Fu; Mengxin Xing; Yuyu Wang; Linwei Yang; Di Wang; Taolin Fan; Bang Xiao; Shengwen Niu (Fishes, 2026)
C-type lectins (CTLs) are important pattern recognition receptors (PRRs) involved in innate immune defense in crustaceans. In this study, a novel C-type lectin, designated LvCTL, was identified and functionally characterized from Litopenaeus vannamei. Sequence analysis revealed that the open reading frame (ORF) of LvCTL is 495 bp in length and encodes a 164-amino acid polypeptide containing a typical C-type lectin-like domain but lacking the classical carbohydrate-binding motifs. Notably, two novel EPF motifs were identified in the CTLD region, suggesting a potential non-canonical ligand recognition pattern. Phylogenetic analysis revealed that LvCTL clustered with other crustacean CTLs. Tissue expression analysis revealed that LvCTL exhibited the highest transcript level in the hepatopancreas. After immune stimulation, LvCTL expression in the hepatopancreas was significantly regulated by LPS, Vibrio parahaemolyticus, Staphylococcus aureus, WSSV and Poly(I: C), indicating its involvement in antimicrobial immune responses. RNA interference assays showed that knockdown of LvCTL significantly increased the bacterial burden and reduced the survival rate of shrimp after V. parahaemolyticus infection. Furthermore, recombinant LvCTL displayed broad bacterial binding activity to Gram-negative and Gram-positive bacteria and induced calcium-dependent agglutination of V. parahaemolyticus and S. aureus. Taken together, these results demonstrate that LvCTL functions as an important immune recognition molecule and contributes to antibacterial defense against V. parahaemolyticus in L. vannamei. These findings broaden our understanding of the functional diversity of shrimp CTLs and their contributions to crustacean innate immunity.

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Chlor(am)ination of algal bound extracellular polymeric substances and cellular responses during raw water pre-chlorination - Qi Fu; Tian-Yang Zhang; Chao Zeng; Zheng-Xiong Zheng; Jun Shi; Zhu Peng; Zhen-Ning Luo; Huan He; Qian Xiao; Xi Wang; Bin Xu (Journal of Hazardous Materials, 2026)

Constructing Fe3N/MnO heterojunction via heteroatom doping for degrading dye wastewater by heterogeneous electro-fenton system - Yi Wang; Yunliang Fan; Xiaocong Liu; Fuping Zhang; Hangdao Qin; Bo Xing; Xingyong Liu; Chaoting Fu; Yan Luo; Guo Yang; Ning Gou (Journal of Environmental Sciences, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Hyperspectral phenotyping and GWAS identify novel QTLs for soybean photosynthetic rate - Li Wang; Ning Fu; Jinyu Zhang; Ao Shen; Yuanmeng Yu; Yanhong Wang; Xiaoli Guan; Dan Zhang; Fang Huang; Xiaoyong Yang; Deyue Yu; Zhongwen Huang; et al. (Theoretical and Applied Genetics, 2026)

Simple sequence repeat (SSR) marker-based genetic diversity and population structure of large-leaf tea germplasm across four major tea-producing regions of Yunnan, China - Qihuan Ding; Wuxiang Fu; Ning Chi; Jianmei Su; Shanshan Wu; Zhanxia Ma (Genetic Resources and Crop Evolution, 2026)

Non-fickian CO2CH4 transport in carbonate composite cores analyzed with fractional-order model and in-situ NMR characterization - Miao Zhang; Lianlin Deng; Bo Ning; Jianlin Guo; He Yuan; Ninghai Fu; Luis F. Ayala (Advances in Water Resources, 2026)

Synergistic consolidation of expansive subgrade soils enabled by a novel solid waste-based stabilizer: a sustainable approach - Xin Ji; Ruize Zhao; Xueqiang Cui; Xiaofeng Wang; Ning Fu; Penggang Wang (Transportation Geotechnics, 2026)

Acceleration of Fe2+/Fe3+ cycle in core-shell MIL-88A(Fe)@1T-WS2 heterojunction to promote peroxymonosulfate activation for phenol degradation - Dachao Yan; Hongjin Chen; Ning Fu; Guanguo Zhang; Yuxiang Chen; Peng Wang; Shuai Guo; Xuechang Ren (Process Safety and Environmental Protection, 2026)

Symbiotic chlorine-resistant bacteria and fungi in urban building drinking water plumbing pipe biofilms - Zhen-Ning Luo; Tian-Yang Zhang; Huan He; Ren-Jie Pan; Yun-Qiao Zeng; Zhu Peng; Jun Shi; Qi Fu; Minyuan Pan; Chao Zeng; Qian Xiao; Ling Hu; et al. (Journal of Hazardous Materials, 2026)

1D-confined gravity-driven liquid template strategy to construct high thiophene-S doping gully-shaped carbon nanorods for efficient sodium storage - Ming Zhao; Wenlei Jia; Huihui Zhao; Chao Zhang; Miaomiao Li; Jing Wang; Tengfei Wei; Chuanxiang Zhang; Ning Fu (Chemical Engineering Journal, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Shear performance of prefabricated utility tunnel joints considering the effect of connectors - Chao Zhang; Jiao-jiao Chen; Wei-ning Zhong; Xin Li; Chen-chen Sun; You-jun Xu; Xin Han; Jun-yi Gao; Jian-jun Wang; Zhi-qiang Fu (Tunnelling and Underground Space Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Natural water constituents boost pollutant removal in the O3/PAA system via Cu-doped LaFeO3 perovskite and in-situ formed metal complexes - Zhenyang Xu; Shuhan Fu; Zijing Ling; Shouling Li; Fengling Pan; Ning Xiao; Shuguang Wang; Tingting Zhang (Journal of Environmental Chemical Engineering, 2026)

Phase-modulated engineering of oxygen-doped molybdenum disulfide for boosting visible light-driven photocatalytic tetracycline degradation - Ze Yuan; Chenghao Li; Nan Feng; Xinping Fu; Yuting Ning; Wei Yao; Lepu Ci; Jun Cui (Journal of Environmental Chemical Engineering, 2026)

Synergistic effect of high-voltage alternating and static electric fields on quality maintenance of partially frozen Litopenaeus vannamei via stabilization of protein structure - Zekai Fan; Chen Li; Bing Chen; Ning Wang; Man Fu; Donglei Luan; Zunying Liu; Kaining Han; Shiyuan Dong (Food Chemistry, 2026)

Stratosphere–monsoon superposition drives summertime surface ozone extremes on the Tibetan Plateau - Wenlin Chen; Xiaoliang Qin; Shikang Tao; Yanyu Wang; Ying Wang; Zibing Yuan; Suona Zhuoga; Huifang Zhang; Qingyan Fu; Zhi Ning (Environmental Pollution, 2026)

Synergistic induction of immunogenic cell death and tumor microenvironment remodeling by biotinylated marine polysaccharide nanoparticles for enhanced colorectal cancer therapy - Hui Wang; Haoyu Yu; Yan Yang; Mengying Fu; Lihua Geng; Jing Wang; Yang Yue; Quanbin Zhang; Ning Wu (Carbohydrate Polymers, 2026)

Integrating Time and Frequency Domain Features of fMRI Time Series for Alzheimer’s Disease Classification Using Graph Neural Networks - Wei Peng; Chunshan Li; Yanhan Ma; Wei Dai; Dongxiao Fu; Li Liu; Lijun Liu; Ning Yu; Jin Liu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Exploration Biomarkers for Recurrence of Hepatocellular Carcinoma After Liver Transplantation Based on Bioinformatics Analysis - Guangyi Zhu; Shijian Li; Ziyang Luo; Ning Wen; Haibin Li; Yang Fu; Weixuan Li; Jihua Wu; Xuyong Sun (Biochemical Genetics, 2026)

Nighttime Atmospheric Pressure Measurement at 80–110 km Altitude over Xi’an by GBAVTII - Cun-Xia Li; Yang-He Liu; Yan Fang; Ning-Ju Hui; Yan-Long Wang; Yi-Shan Zhang; Di-Di Fu; Yuan-He Tang (Applied Geophysics, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

A comprehensive flavor evaluation method for drinking water based on flavor rating assessment (FRA) and the flavor wheel, incorporating benchmark referencing and objective weighting - You Lyu; Huan He; Zhen-Ning Luo; Tian-Yang Zhang; Xin-Li Huang; Zhu Peng; Qi Fu; Xin-Bai Jin; Bin Xu (Journal of Water Process Engineering, 2026)

High-entropy strategy towards structurally stable garnet solid electrolyte for ultra-long lifespan solid-state lithium batteries - Shiyu Yu; Shihao Fu; Pingmei Li; Mingxin Zhang; Yaqing Wei; De Li; Liang Yang; Daming Chen; Ning Wang; Yong Chen (Chemical Engineering Journal, 2026)

SF-based electro-responsive conductive composite NGCs promote peripheral nerve regeneration by inhibiting ferroptosis in Schwann cells - Guanjie Han; Tengfei Fu; Xingdong Xiang; Ping Wei; Lei Huang; Ning Wang; Mengxuan Bian; Shunyi Lu; Dihan Su; Jiayi Wang; Libo Jiang; Jian Zhang (Chemical Engineering Journal, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

ECCAS: An interactive web platform for assessing water-sustainable ecosystem productivity in large-scale dryland restoration - Ning Chen; Fen Gou; Weibin Zhang; Xinyao Xu; Nan Gao; Shuai Li; Bojie Fu; Yihe Lü; Shuai Wang; Jianwu Yan; Wei Liang (Journal of Environmental Management, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

A non-destructive workflow integrating X-ray computed tomography and machine learning for multi-defect identification and kernel plumpness assessment of in-shell walnuts - Menglong Ma; Ming Zhang; Haitao Fu; Yixiao Wang; Ning Yang; Huang Dai; Fuwei Pi; Xiaodan Liu; Jiahua Wang (Food Control, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Interface adsorption and repulsion dual regulation for unidirectional ion transport and stable power generation from moisture - Mingyong Xin; Chunqiao Fu; Ning Zhang; Junjie Hao; Tingting Yang; Linmao Qian (Chemical Engineering Journal, 2026)

Oriented hetero-phase engineering modulates spontaneous polarization and band alignment - Yumin Wang; Zhenfei Fu; Zewei Zheng; Cheng Gao; Suiting Ning; Yun Tang; Wei Zeng; Pengfei Fang; Yi Xiong (Chemical Engineering Journal, 2026)

Construction Disturbance Effects of Tunnelling in Completely Decomposed Granite and Reinforcement Using Interlocked Pipe Roofs - Junfu Fu; Maoquan Ning; Junru Zhang; Ziyan Fan; Jintao Fu; Yangfan Wu; Xuehui Jin; Jimeng Feng; Yumeng Liu (Geotechnical and Geological Engineering, 2026)

Spatial evolution and driving factors of surface water chemistry in the Duliujiang River Basin, Southwest China - Zhiyong He; Hang Li; Zengping Ning; Jinshuai Fu; Yanqiong Luo; Qianchen Liu; Wenjia Lu; Yizhang Liu; Jing Sun; Chengshuai Liu (Acta Geochimica, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Sulfur vacancies in Z-scheme ZnS/MIL-88A(Fe) heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced OFX degradation - Xuechang Ren; Bowen Zheng; Xingyu Liu; Hongjin Chen; Deze Yang; Zhongshan Li; Ning Fu; Yong Zhang (Process Safety and Environmental Protection, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Freeze-thaw cycles intensified the synergistic inhibitory effects of enrofloxacin and UV-328 on rye seedling growth - Ning Li; Guozhang Bao; Simeng Chen; Yanan Xu; Yue Yuan; Zimin Fu (Journal of Environmental Management, 2026)

Accelerated activation of ozone on Fe-doped MnO2 for highly efficient ozone catalytic oxidation of ethyl acetate - Ning Wu; Ming Ouyang; Lei Liu; Chuying Qiu; Ning Wang; Peirong Chen; Junliang Wu; Xiaofei Song; Mingli Fu; Daiqi Ye (Journal of Environmental Sciences, 2026)

Construction of a novel Mn3O4/NiCo2S4 composite catalyst for enhanced peroxymonosulfate activation toward rapid degradation of ofloxacin: Mechanistic and toxicity assessment - Xuechang Ren; Zhongshan Li; Duxudong Huang; Deze Yang; Bowen Zheng; Jianzhao Wang; Ning Fu (Environmental Research, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Analytical Model for the Toppling Fracture Depth of Antidip Layered Rock Slopes Under Seismic Loading - Yang Wang; Fei Ye; Leilei Jin; Ning Sun; Shuang Yao; Wenxi Fu (Rock Mechanics and Rock Engineering, 2026)

The CBL and CIPK Gene Family in Cucumber (Cucumis sativus): Genome-Wide Analysis and Expression Profiles in Response to Abiotic and Biotic Stresses - Ning Wang; Yu Fu; Yuke Li; Erfang Kang; Zhonglin Shang (Plant Molecular Biology Reporter, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Molecular crystal memristor-based edge AI platform for energy-efficient and real-time smart grid inspection - Pengfei Guan; Lanhao Qin; Ke Ning; Jie Liu; Decai Ouyang; Yimeng Yu; Jinsong Wu; Xing Lu; Yingshuang Fu; Yuan Li; Huiqiao Li; Tianyou Zhai (Science Bulletin, 2026)

Hollow NiCo₂S₄ microspheres synergistically promote peroxymonosulfate activation for efficient ofloxacin degradation: Performance, mechanism and degradation pathways - Zhongshan Li; Xuechang Ren; Guanguo Zhang; Duxudong Huang; Gongrong Chen; Huiying Lei; Yaoling He; Ning Fu (Journal of Water Process Engineering, 2026)

Compound-specific isotopic fingerprints of lacustrine n-alkanes in the middle reaches of the Yangtze river basin associated with their environmental significance - Jiayi Guo; Minhan Sun; Letian Ning; Hong Wang; Pengyuan Fu; Mingli Zhang; Yanhua Wang (Journal of Soils and Sediments, 2026)

Selective elimination of aniline contaminants induced by semiquinone radicals during peracetic acid oxidation of dihydroxybenzenes - Renjie Pan; Zheng-Xiong Zheng; Huan He; Tian-Yang Zhang; Chao Zeng; Qi Fu; Zhen-Ning Luo; Chen-Yan Hu; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Large model-driven physical neural network architecture: Coupled multi-environmental factors for vessel drift trajectory prediction - Fengqi Li; Lingchen Fu; Xuefeng Du; Xin Zhang; Huilin Cheng; Ning Tong; Fengqiang Xu (Ocean Engineering, 2026)

Carbon isotope stratigraphy of the Doushantuo Formation in basinal facies of South China: Constraints on the Shuram excursion in a deep ocean environment - Rui Fu; Chaochao Xing; Lei Zhang; Meng Ning; Fangbing Li; Xianguo Lang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

From land to sea: Natural products as promising agents against hyperuricemia - Mengying Fu; Roger Hunter; Ammad Ahmad Farooqi; Quanbin Zhang; Jing Wang; Lihua Geng; Yang Yue; Yan Yang; Ning Wu (Food Bioscience, 2026)

Construction of small polarons in Ni2P for rapid catalytic conversion of polysulfides in lithium-sulfur batteries - Shujun Liu; Pengcheng Yao; Jun Jiang; Tong Guo; Zhijie Qi; Yunfan Zhang; Ning Zhang; Yefang Teng; Tao Chen; Xin Wang; Junwu Zhu; Yongsheng Fu (Chemical Engineering Journal, 2026)

Mechanical interlocking enhanced hybrid electrode for long-term epidermal biopotential monitoring in clinical applications - Xiaoqian Dong; Fu Fan; Lei Chen; Yu Zhou; Fangqun Cheng; Yinglong Duan; Ning Qin; Huan Cao; Xingxing Wang; Bo Feng; Jianfei Xie; Jian Zhou; et al. (Chemical Engineering Journal, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Differential response of anode and cathode in dual chamber microbial electrochemical system for treatment of antibiotic and microplastic composite polluted wastewater - Nuchao Xu; Chuanning Xiao; Huilin Yin; Yun Fan; Zhenyu Ding; Ning Sun; Quankai Fu; Aizhong Ding (Journal of Cleaner Production, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Co-gelatinization with rutin nanoparticles for regulating rice starch digestibility - Shupin Ye; Yuteng Fu; Fangjian Ning; Jianyong Wu; Shunjing Luo; Jiangping Ye; Chengmei Liu (Food Hydrocolloids, 2025)

Preparing both mechanically robust and highly conductive semi-solid supercapacitor using environment-friendly gelatin-based hydrogel with cellulose fibers and ionic liquid - Yunxia Yang; Dan Li; Ningguo Yang; Tengfei Yan; Yangbing Wen; Ning Yan; Fu Guo (Chemical Engineering Journal, 2025)

Synergistic performance enhancements of shear stiffening gel via dynamic-covalent copolymerization and carbon nanotube integration - Ting Fan; Yuanqing Li; Yu Zhu; Yuqin Mao; Ning Hu; Pei Huang; Shaoyun Fu (Chemical Engineering Journal, 2025)

Genome-Wide Analysis of CPK and CRK Gene Families in 10 Cucurbitaceae Species and Responses To Abiotic Stresses in Cucumber - Ning Wang; Yu Fu; Yuke Li; Erfang Kang; Zhonglin Shang (Tropical Plant Biology, 2025)

3D Geomechanical Modeling for Sweet Spot Identification in Thin-Layer Carbonate Reservoirs - Jian Yang; Zhouyang Wang; Miao Yang; Yuanyu Yang; Xucheng Li; Le Luo; Yan Fu; Man Huang; Zhi Zhong; Dongchao Su; Zikun Li; Fulong Ning (Geotechnical and Geological Engineering, 2025)

Short-term no-tillage improves soil water retention and maintains soil aeration at high moisture conditions despite reduced macroporosity - Jing Tan; Bingcheng Si; Ying Zhao; Yili Lu; Yuxin Chen; Ning An; Song Li; Weichao Wang; Han Fu; Wei Han; Yanli Yi (Soil and Tillage Research, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

How does thinning affect the photosynthetic parameters and their responses to environmental factors in a subtropical plantation? - Mingjie Xu; Shengtong Li; Fengting Yang; Tao Zhang; Qingkang Li; Zeqing Ma; Xianjin Zhu; Xiaoli Fu; Xiaoqin Dai; Jiaxin Song; Ning Chen; Jiaxing Zu; et al. (Forest Ecology and Management, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Smart dual-channel fluorescent sensor overcoming cross-interference: Visual detection of Cu(II) and doxycycline in multiple scenarios, and precise discrimination of tetracycline analogs - Yingqi Yuan; Liuqing Fu; Lina Zhang; Jun Xu; Ning Bi; Yongxin Li; Lei Jia (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Lighting effects on visual and cognitive adaptation in multimedia classrooms: a multimodal neurophysiological study - Mengrui Wang; Ning Guo; Yutao Liu; Yitao Fu; Xiang Zhou (Building and Environment, 2025)

A nine-year statistical study on the thunderstorms generated amid Dabie vortex background - Xue Xiao; Shen-Ming Fu; Bo Wang; Chao-Ying Yang; Shu-Guang Ning; Shi-Jun Sun; Kun-Shuang Zhu; Jian-Hua Sun (Atmospheric Research, 2025)

Creation of new rice germplasm with cross-resistance to auxin herbicides picloram and dicamba by genome editing of OsAFB4 - Haonan Wei; Dongling Li; Kexin Xie; Siying Lou; Guojun Dong; Fu Guo; Guiwei Lian; Xiangjian Pan; Zhanghui Zeng; Ning Han; Zhenyu Gao; Hongwu Bian (Theoretical and Applied Genetics, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Ubiquitin-conjugating enzyme StUBC19 regulates osmotic and salt stress in potato transgenic plants - Xue Fu; Xun Tang; Ning Zhang; Xinyu Ren; Peishan Li; Huaijun Si (Plant Science, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Mechanistic study on the enhanced activation of peroxymonosulfate by the bimetallic Mo/Co Co-doped g-C₃N₄ composite catalyst 8-CNMC for phenol degradation: Applicable for neutral and alkaline condition - Xuechang Ren; Miao Tian; Ning Fu; Hongjin Chen; Zuoyan Chen; Yajun Wei; Qiongqiong Wang (Journal of Environmental Chemical Engineering, 2025)

Magnetic recyclable MIL-88A(Fe)@WS2/CuFe2O4 ternary composite promotes peroxymonosulfate activation for efficient phenol removal: Performance, mechanism and toxicity evaluations - Ning Fu; Yuxiang Chen; HongJin Chen; Bowen Zheng; Miao Tian; Qiongqiong Wang; Xuechang Ren (Journal of Environmental Chemical Engineering, 2025)

Tea polyphenol–functionalized sewage sludge ash for efficient Cr(VI) removal: A sustainable approach to waste valorization - Xingyu Liu; Guangzheng Zhou; Hexu Yang; Ning Liu; Dun Fu; Tonni Agustiono Kurniawan (Journal of Environmental Chemical Engineering, 2025)

Stepwise recovery of gallium (Ga), lithium (Li), and rare earth elements (REEs) from roasted coal gangue based on leaching kinetics differentiation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Kejia Ning; Biao Fu; Lin Ma; Xin Sun; Yuntao Kang; Mengting Hong; Guixia Fan; Xiahui Gui; Jiushuai Deng (Hydrometallurgy, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Regional variations in vegetation greening and climate change impacts on gross primary productivity and evapotranspiration in the Loess Plateau - Fen Gou; Wei Liang; Bojie Fu; Ning Chen; Weibin Zhang; Zhao Jin; Jianwu Yan; Yihe Lv; Xingguo Mo; Nan Gao (Agricultural and Forest Meteorology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Scaling of urban residential building stock system and carbon emissions accounting for vacant houses in China - Wanru Leng; Guangxin Liu; Xiaoyu Cheng; Yang Li; Shoujuan Tang; Jun Ning; Yuanhang Li; Hang Fu; Lei Shi (Resources, Conservation and Recycling, 2025)

Functional characterization of RNAi candidate target genes in Monolepta hieroglyphica (Motschulsky) for potential pest control applications - Xu Chen; Ning Fu; Qingxuan Xu; Chun Zhang; Su Wang; Da Xiao (Journal of Asia-Pacific Entomology, 2025)

Fluorine-rich MOFs-based composite solid electrolytes realizing fast Li+ transportation kinetics and dendrite-free interface - Xiaoyang Niu; Chenjun Ju; Da Xu; Tiantian Wang; Ning Fu; Zhenglong Yang (Chemical Engineering Journal, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Integrating photo-Fenton-like Fe3O4/CdS-O modules into sponge-based gel solar evaporator for synergistic water regeneration and pollutant degradation - Xuyao Qiao; Shuguang Ning; Hongyao Zhao; Ruiting Ni; Wanyu Zhang; Yangping Zhang; Linzhi Zhai; Danhong Shang; Yanyun Wang; Tongyi Yang; Mengnan Wang; Fu Yang (Journal of Environmental Chemical Engineering, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Calculation method and application of discontinuous longitudinal deformation of shield tunnels considering variable stiffness of the ring joints - Yanbin Fu; Ning Liang; Yuehua Guo; Xiangsheng Chen; Ze Wu; Gendi Yelv; Xiaoping Li (Tunnelling and Underground Space Technology, 2025)

Unveiling the ∼110 Ma continental arc in South China: geochemical and isotopic insights from offshore magmatic records in the East China Sea Basin - Lichen Hu; Ning Li; Xiaowei Fu; Xianjun Tang; Kailong Feng; Weilin Zhu; Xi Xu (Gondwana Research, 2025)

Super-large-scale triaxial tests to study the effect of particle size on dynamic characteristics of gravelly soils - Fanwei Ning; Degao Zou; Gengyao Cui; Jingmao Liu; Duo Li; Yongkui Fu (Bulletin of Engineering Geology and the Environment, 2025)

TGEV NSP1 enhances viral replication through antagonizing stress granule formation - Yutong Tang; Yue Zhang; Ning Yang; Han Shi; Yuguang Fu; Bingrong Bai; Baoyu Li; Bin Yang; Guangliang Liu (Veterinary Microbiology, 2025)

Does high-speed railway aggravate environmental inequality in China? - Yun Wang; Lin Fu; Xiaohua Sun; Ning Jia (Transportation Research Part D: Transport and Environment, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Human presence in the southeastern Tibetan Plateau after the Last Glacial Maximum - Jia-Jing Wang; Pei-Yang Tan; Yue Feng; Zhe-Xuan Zheng; Yu-Jie Guo; Jia-Ning He; You-Ping Wang; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effective degradation of phenol using magnetic MoS2/SnFe2O4 composite activated peroxysulfate: Mechanism study and catalytic performance evaluation - Gongrong Chen; Xuechang Ren; Zhongshan Li; Hongjin Chen; Huiying Lei; Guanguo Zhang; Duxudong Huang; Ning Fu (Journal of Environmental Chemical Engineering, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Cobalt phthalocyanine modified holey Graphene/Cobalt phosphide for supercapacitor electrodes - Wei Chen; Min Fu; Siyuan Yang; Liangmin Ning; Hao Yu; Meng Gao; Kunhua Wang; Meili Guan; Ruitao Lv; Nan Li; Jianming Pan (Chemical Engineering Journal, 2025)

Quantifying impact of different surface covers on sediment transport capacity: Insights from flume experiments - Kai Zhang; Ning Li; Suhua Fu; Dike Feng (CATENA, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Evaluation of muscle quality and movement-related traits in two common carp strains under a rice–fish farming system - Yating Gong; Mingkun Luo; Xianbo Zhang; Ning Qin; Wenbin Zhu; Lanmei Wang; Jianjun Fu; Zaijie Dong (Aquaculture International, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Influence of surface cover type on sediment transport capacity and sediment retardation benefits based on flume experiments - Kai Zhang; Ning Li; Suhua Fu; Hongli Mu (Soil and Tillage Research, 2025)

Multi-method data-driven prediction for maximum scour depth of pile foundations in clay - Qing-Kai Song; Wen-Gang Qi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2025)

Effects of ferrite porous confined biochar nanoreactor on the adsorption and desorption of Pb and Cd - Ning Liu; Rongxin Zhou; Shuangxue Huang; Jiming Zhang; Hongda Zhang; Hang Liu; Xiao Du; Dongyi Zhang; Renlong Zhang; Zhentao Sun; Shifeng Fu; Xiumei Zhan (Journal of Water Process Engineering, 2025)

Manganese vacancy and shell protection as two-pronged strategies for boosting capacitive deionization of manganese-based prussian blue analog electrodes - Guoxiang Liu; Wei Chen; Liangmin Ning; Hao Yu; Meng Gao; Linzheng Ma; Ruitao Lv; Jianming Pan; Min Fu (Desalination, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Nrf2 deficiency aggravates hepatic cadmium accumulation, inflammatory response and subsequent injury induced by chronic cadmium exposure in mice - Chengjie Chen; Xue Han; Ning Xu; Wei Shen; Gang Wang; Junying Jiao; Weiwei Kong; Jiaxin Yu; Jingqi Fu; Jingbo Pi (Toxicology and Applied Pharmacology, 2025)

10Be records of the Matuyama-Brunhes polarity reversal in the northeastern Chinese loess Plateau - Ling Tang; Weijian Zhou; Xisheng Wang; Feng Xian; Xianghui Kong; Yajuan Du; Jie Zhou; Guoqing Zhao; Yunchong Fu; Ning Chen (Quaternary Science Reviews, 2025)

The mechanism of surface cover influences the sediment transport capacity - Kai Zhang; Ning Li; Suhua Fu; Hongli Mu; Bingjun Lu (Journal of Hydrology, 2025)

The colorimetric identification chips of artificial visual recognition and rapid digital response for detecting pollutants - Shichao Guo; Li Wang; Lin Hu; Qiangqiang Tao; Qiuyan Hu; Fu Feng; Wei Jin; Chuanbin Li; Ning Hu (Journal of Cleaner Production, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

The re-precipitation and photo-induced cerium ions release of commercial cerium sulfide pigment in aqueous phase - Ning Li; Linzi Zuo; Fanchao Xu; Xiaolei Qu; Heyun Fu; Huiting Liu (Environmental Pollution, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

The effect of particle shape on particle breakage and shape evolution in gravelly soils - Fanwei Ning; Degao Zou; Gengyao Cui; Jingmao Liu; Duo Li; Yongkui Fu (Transportation Geotechnics, 2025)

Irradiation and DOM mediate lead release from polyvinyl chloride microplastics in natural surface water - Mingyang Zhang; Yu Zeng; Qinglong Fu; Peixin Cui; Ning Chen; Yujun Wang; Dongmei Zhou; Guodong Fang (Journal of Hazardous Materials, 2025)

Parameter optimization of the observation system for the South Yellow Sea strong shielding layer based on seismic illumination analysis - Jia-Jia Yang; Jian-Wen Chen; Fu-Qiang Huang; Zhong-Hui Yan; Bao-Hua Lei; Xiao-Jie Wang; Hua-Ning Xu; Hong Liu (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Electrostatically self-assembled Fe3O4@Ti3C2Tx electrodes for efficient capacitive deionization driven by ultrafast ion pumps - Fu Feng; Li Wang; Ning Hu; Zhuang Ren; Yuhe Bai; Qiangqiang Tao; Kang Li; Shuai Lu; Aixin Zhang; Qingmiao Wang (Journal of Environmental Chemical Engineering, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

3D adaptive finite-element forward modeling for direct current resistivity method using geometric multigrid solver - Ce Qin; Wenliang Fu; Ning Zhao; Jun Zhou (Computers & Geosciences, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Mechanism of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid toxicity in Carassius auratus through the microbiota–gut–brain axis - Xue Jiao; Faye Zhang; Lei Guo; Zheng-Yao Guo; Qiu-Shuang Fu; Cheng-Cheng Bi; Xian-Wei Hou; Ning Wang; Jing-Xiang Zhou; Yue-Hong Li (Aquaculture, 2025)

Substance flow analysis of polyethylene terephthalate (PET) fiber in China - Jun Ning; Shoujuan Tang; Yingjie Fu; Guangxin Liu; Yuheng Sun; Zhengyuan Feng; Donggen Huang; Lei Shi (Resources, Conservation and Recycling, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Advances in the synthesis and properties of sulfur quantum dots for food safety detection and antibacterial applications - Yihong Huang; Yujia Liu; Ning Fu; Qitong Huang; Hanqiang Zhang (Food Chemistry, 2025)

Ultra-adhesive iontronic hydrogels strengthened by folded protein for flexible transducer with language recognition capabilities - Mansoor Khan; Luqman Ali Shah; Jun Fu; Fanghua Ning; Hyeong-Min Yoo (Chemical Engineering Journal, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Changes in the key odorants of loose-leaf dark tea fermented by Eurotium cristatum during aging for one year: Focus on the stale aroma - Shanshan Shen; Jialin Fu; Ranqin Fan; Jixin Zhang; Haoran Sun; Yu Wang; Jingming Ning; Pengxiang Yue; Liang Zhang; Xueling Gao (Food Research International, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Evidence for archaeal metabolism of D-amino acids in the deep marine sediments - Yang Yu; Ning-Hua Liu; Zhao-Jie Teng; Yin Chen; Peng Wang; Yu-Zhong Zhang; Hui-Hui Fu; Xiu-Lan Chen; Yu-Qiang Zhang (Science of The Total Environment, 2024)

Abrupt shift in the organic matter input to sediments in Lake Liangzi, a typical macrophyte-dominated shallow lake in Eastern China, and its response to anthropogenic impacts - Yongdong Zhang; Ning Liu; Weizhen Lei; Huan Fu; Zhengwen Liu (Science of The Total Environment, 2024)

A new split-ring protoilludane-type sesquiterpenoid and prenylated aromatic compounds from Coriolopsis trogii - Xin-Meng Zhai; Lu-Lu Wang; Ning Li; Fu-Cai Ren (Phytochemistry Letters, 2024)

The preparation and characterization of WS2 nanomaterials with different morphologies and the mechanistic study of peroxymonosulfate activation for phenol degradation - Xuechang Ren; Zhenyu Yang; Xuchuang Pang; Hongjin Chen; Ning Fu (Journal of Environmental Chemical Engineering, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

The phytoplankton community affects the energy metabolism and immunomodulation strategy of oyster during breeding seasons - Zhaoqun Liu; Ning Kong; Yukun Zhang; Yan Zheng; Chuanyan Yang; Qiang Fu; Ziyang Zhang; Fuzhe Li; Ranyang Liu; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Salt Stress Induces Complicated miRNA Responses of Sugar Beet (Beta vulgaris L.) - Ziqiang Zhang; Zengjuan Fu; Wenjin Chen; Liang Wang; Shangmin Zhao; E Yuanyuan; Hui Zhang; Bizhou Zhang; Mengyuan Sun; Wenzhe Zheng; Jing Dong; Zhiqi Zhang; et al. (Sugar Tech, 2024)

Applewood Biochar at Different Smoldering Conditions Passivates Pyrite by Promoting the Formation of Jarosite - Hecheng Fu; Jiale Fan; Jie Li; Jianhong Huang; Senlin Tian; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Fatty acid degradation driven by heat during ripening contributes to the formation of the “Keemun aroma” - Wenjing Huang; Qiuyan Liu; Xiaoxue Fu; Yida Wu; Zihao Qi; Guofu Lu; Jingming Ning (Food Chemistry, 2024)

A new 3D printing strategy by enhancing shear-induced alignment of gelled nanomaterial inks resulting in stronger and ductile cellulose films - Yunxia Yang; Dan Li; Ning Yan; Fu Guo (Carbohydrate Polymers, 2024)

Oscillating water column wave energy converter arrays coupled with a parabolic-wall energy concentrator in regular and irregular wave conditions - Robert Mayon; Dezhi Ning; Jin Xu; Lei Fu (Coastal Engineering, 2024)

Design and implementation of low-cost geomagnetic field monitoring equipment for high-density deployment - Lu-Qiang Sun; Xian-Fu Bai; Jian Kang; Ning Zeng; Hong Zhu; Ming-Dong Zhang (Applied Geophysics, 2024)

Effects of shading & calcium peroxide suspension on landscape water quality and CH4 and N2O production - Tian-Tian Fu; Yi Wang; Hui-Ying Zhao; Zhen-Hao Liang; Kai Zhang; Yue-Ning Wang; Hui-Long Ouyang; Jia-Ni Yin; Yong-Qiang Liu (Journal of Water Process Engineering, 2024)

High-accuracy quantitative model for phosphate anions in solution based on absorption spectroscopy and machine learning algorithms - Rong Zhang; Linhua Jiang; Ning Duan; Weisong Fu; Jun Ma; Xiaolu Sun; Jiaqi Liao; Hao Jin (Journal of Cleaner Production, 2024)

Activity of CuCoCe layered double hydroxides catalysts and mechanism for C3H6-SCR - Jiayin Chen; Wei Fu; Chen Cai; Shuying Ning; Muhammad Kashif; Wenyi Deng; Bingtao Zhao; Yaxin Su (Fuel, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

High Thiophene-S doped soft carbons for sodium storage - Huihui Zhao; Wanyu Shang; Chao Zhang; Haixiang Song; Changwei Lai; Chuanxiang Zhang; Ning Fu (Chemical Engineering Journal, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Two new diarylheptanoids from the green walnut husks of Juglans mandshurica Maxim. - Yuan-Yuan Zhou; Ning-Yu Liu; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Qi-Feng Fu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2024)

Spatial compartmentalization and temporal stability of associated microbiota in Pacific oyster Crassostrea gigas - Qiang Fu; Zichao Yu; Junyan Zhao; Lei Gao; Ning Kong; Lingling Wang; Linsheng Song (Journal of Oceanology and Limnology, 2024)

Improving water quality and mitigating CH4 and N2O production in urban landscape water simultaneously by optimizing calcium peroxide dosage - Zhen-Hao Liang; Yi Wang; Hui-Ying Zhao; Tian-Tian Fu; Yong-Qiang Liu; Kai Zhang; Yue-Ning Wang; Hui-Long Ouyang; Jia-Ni Yin (Science of The Total Environment, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Understanding the metal-electrode-correlated degradation of organic solar cells under illumination/thermal stress - Zhipeng Yin; Huan Zhao; Lijun Chen; Yunjie Li; Xingyu Liu; Jianfei Fu; Hai-Qiao Wang; Ning Li (Chemical Engineering Journal, 2024)

Hydrodynamic performance of a land-based multi-chamber OWC wave energy capture system: An experimental study - Dezhi Ning; Lei Fu; Yu Zhou; Robert Mayon; Yuhang Zhang (Coastal Engineering, 2024)

Nitrogen migration and transformation during re-suspension and photo-induction in landscape water replenished by reclaimed water - Hui-Ying Zhao; Zhen-Hao Liang; Kai Zhang; Jia-Ni Yin; Tian-Tian Fu; Yue-Ning Wang; Hui-Long OuYang; Yi Wang (Environmental Science and Pollution Research, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Formation of reactive intermediates in paddy water from different temperature zones for the promotion of abiotic ammonification - Yu Zeng; Mingyang Zhang; Qinglong Fu; Ning Chen; Yujun Wang; Dongmei Zhou; Guodong Fang (Water Research, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Hypoxia inducible factor-1α facilitates transmissible gastroenteritis virus replication by inhibiting type I and type III interferon production - Yunhang Zhang; Xue Rui; Yang Li; Yue Zhang; Yifei Cai; Chen Tan; Ning Yang; Yuanyuan Liu; Yuguang Fu; Guangliang Liu (Veterinary Microbiology, 2024)

Natural and anthropogenic influences on sterol geochemical characteristics in lake sediments and implications for using sterols as paleoenvironmental indicators - Yongdong Zhang; Ning Liu; Huan Fu; He Cui; Zhengwen Liu (Journal of Hydrology, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Enhanced mitigation of N2O and NO emissions through co-application of biochar with nitrapyrin in an intensive tropical vegetable field - Changhua Fan; Youfeng Leng; Xiaotong Wang; Junjiao Wang; Yajun Fu; Xiaomin Huang; Wenlong Gao; Wen Zhang; Huiran Liu; Ziyu Ning; Qinfen Li; Miao Chen (Agriculture, Ecosystems & Environment, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Robust and ultra-tough lignocellulosic organogel with zipper-like sliding noncovalent nanostructural design: Towards next-generation bio-derived flexible electronics - Haonan Zhang; Yanchen Zhu; Tongtong Fu; Cheng Hao; Yang Huang; Hao Ren; Ning Yan; Huamin Zhai (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effective degradation of phenol by activating PMS with bimetallic Mo and Ni Co-doped g C3N4 composite catalyst: A Fenton-like degradation process promoted by non-free radical 1O2 - Miao Tian; Xuechang Ren; Suying Ding; Ning Fu; Yajun Wei; Zhenyu Yang; Xiaoqing Yao (Environmental Research, 2024)

Effect of long-term straw return on organic matter transformation by hydroxyl radical during paddy soil oxygenation - Yanqi Xiao; Wei Peng; Junhong Fu; Yaqi Ning; Hao-jie Cui; Dong Cheng; Na Zhang; Weijun Zhou; Wenjuan Liao (Chemical Engineering Journal, 2024)

Heterostructure nanozymes with sustainable tumor microenvironment regulation and reinforced hyperthermia-responsive catalytic activities for orchestrated osteosarcoma catalytic therapy - Xing Zhang; Xiang Li; Mengying Fu; Jeremiah Ong'achwa Machuki; Wandong Wang; Liang Wu; Qun Zhao; Ning Xin; Lei Hua; Fenglei Gao (Chemical Engineering Journal, 2024)

Does mutualism provide additional indirect benefits? Behavioral indicators of chemical communication in a temporally dynamic fish-mussel mutualism - Ning Zhang; Chris K. Elvidge; Qinlei Li; Shijian Fu; Jigang Xia (Behavioral Ecology and Sociobiology, 2024)

Phosphate activated geopolymer-based coating with high temperature resistance for sub-ambient radiative cooling - Ning Yang; Qingdong Xuan; Yang Fu; Xue Ma; Dangyuan Lei; Jianlei Niu; Jian-Guo Dai (Sustainable Cities and Society, 2024)

Twelve pathways of carbon neutrality for industrial parks - Yuheng Sun; Yuanhang Li; Jun Ning; Hang Fu; Fangtao Liu; Zhengyuan Feng; Guangxin Liu; Lei Shi (Journal of Cleaner Production, 2024)

C vacancy and F decorated g-C3N4 for boosting photocatalytic ozonation of sodium p-perfluorinated nonoxybenzenesulfonate - Weirui Chen; Siyou Fu; Xukai Li; Jing Wang; Xunan Ning; Liying Bin; Ping Li; Bing Tang; Laisheng Li (Chemical Engineering Journal, 2024)

Effects of Water Saturation and Loading Condition on Rock Tensile Strength: Insights from Acoustic Emission Analysis - Jun Zhu; Jianhui Deng; Po Ning; Ziguo Fu; Xuankun Li; Ronald Y. S. Pak (Rock Mechanics and Rock Engineering, 2024)

Unveiling the role of ABI3 and hub senescence-related genes in macrophage senescence for atherosclerotic plaque progression - Yajuan Fu; Juan Zhang; Qiujun Liu; Lan Yang; Qianqian Wu; Xiaomin Yang; Lexin Wang; Ning Ding; Jiantuan Xiong; Yujing Gao; Shengchao Ma; Yideng Jiang (Inflammation Research, 2024)
Background Atherosclerosis, characterized by abnormal arterial lipid deposition, is an age-dependent inflammatory disease and contributes to elevated morbidity and mortality. Senescent foamy macrophages are considered to be deleterious at all stages of atherosclerosis, while the underlying mechanisms remain largely unknown. In this study, we aimed to explore the senescence-related genes in macrophages diagnosis for atherosclerotic plaque progression. Methods The atherosclerosis-related datasets were retrieved from the Gene Expression Omnibus (GEO) database, and cellular senescence-associated genes were acquired from the CellAge database. R package Limma was used to screen out the differentially expressed senescence-related genes (DE-SRGs), and then three machine learning algorithms were applied to determine the hub DE-SRGs. Next, we established a nomogram model to further confirm the clinical significance of hub DE-SRGs. Finally, we validated the expression of hub SRG ABI3 by Sc-RNA seq analysis and explored the underlying mechanism of ABI3 in THP-1-derived macrophages and mouse atherosclerotic lesions. Results A total of 15 DE-SRGs were identified in macrophage-rich plaques, with five hub DE-SRGs (ABI3, CAV1, NINJ1, Nox4 and YAP1) were further screened using three machine learning algorithms. Subsequently, a nomogram predictive model confirmed the high validity of the five hub DE-SRGs for evaluating atherosclerotic plaque progression. Further, the ABI3 expression was upregulated in macrophages of advanced plaques and senescent THP-1-derived macrophages, which was consistent with the bioinformatics analysis. ABI3 knockdown abolished macrophage senescence, and the NF-κB signaling pathway contributed to ABI3-mediated macrophage senescence. Conclusion We identified five cellular senescence-associated genes for atherogenesis progression and unveiled that ABI3 might promote macrophage senescence via activation of the NF-κB pathway in atherogenesis progression, which proposes new preventive and therapeutic strategies of senolytic agents for atherosclerosis.

Divergent impacts of VPD and SWC on ecosystem carbon-water coupling under different dryness conditions - Chen Zheng; Shaoqiang Wang; Jinghua Chen; Ning Xiang; Leigang Sun; Bin Chen; Zheng Fu; Kai Zhu; Xinlei He (Science of The Total Environment, 2023)

Study on CO-SCR performance of Ce modified OMS-2 catalysts - Chen Cai; Jiayin Chen; Wei Fu; Shuying Ning; Hao Zhou; Muhammad Kashif; Yaxin Su (Journal of Environmental Chemical Engineering, 2023)

Lithiophilic Sn layer via pre-electroplating to realize the uniform stripping/plating for dendrite free Li metal anodes - Wenlong Liu; Jianzong Man; Yiwen Guo; Yehong Du; Kun Liu; Haibang Zhang; Xiaodong Sun; Ning Zhang; Shize Fu; Juncai Sun (Chemical Engineering Journal, 2023)

Insights into the roles of DOM in humification during sludge composting: Comprehensive chemoinformatic analysis using FT-ICR mass spectrometry - Jibao Liu; Ning Wang; Manabu Fujii; Zhen Bao; Jinyi Wei; Zhineng Hao; Qing-long Fu; Rongjun Gao; Jingfu Liu; Yuansong Wei (Chemical Engineering Journal, 2023)

Geolocated social media data for measuring park visitation in Shenzhen, China - Langjiao Li; Qingyun Du; Fu Ren; Lei Huang; Mihai Voda; Pengfei Ning (Urban Forestry & Urban Greening, 2023)

M1 polarization of chicken macrophage HD11 can be activated by duck Tembusu virus via MyD88-NF-κB-mediated signaling pathway - Ningwei Geng; Ji Fu; Zehao Lv; Jing Li; Yuxin Kong; Lei Qu; Zhiyun Guo; Jun Zhao; Liya Zhu; Feng Wang; Cui Zhao; Sidang Liu; et al. (Veterinary Microbiology, 2023)

Impact action of submarine slides on pipelines: A review of the state-of-the-art since 2008 - Ning Fan; Jianxiong Jiang; Tingkai Nian; Youkou Dong; Lin Guo; Cuiwei Fu; Zhuangcai Tian; Xingsen Guo (Ocean Engineering, 2023)

Defects influence photocatalytic NOCM product selectivity by controlling photogenerative carriers - Ning Zhang; Yu Fu; Wenbo Kong; Bingrong Pan; Changkun Yuan; Shuqing Li; He Zhu; Jun Zhang (Journal of Environmental Chemical Engineering, 2023)

Triplet chromophoric dissolved organic matter regulating the phototransformation and toxicity of imidacloprid in paddy water - Yu Zeng; Qinglong Fu; Dionysios D. Dionysiou; Mingyang Zhang; Mabo Li; Bo Ye; Ning Chen; Juan Gao; Yujun Wang; Dongmei Zhou; Guodong Fang (Chemical Engineering Journal, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Multiple Dimensions of using Mesenchymal Stem Cells for Treating Liver Diseases: From Bench to Beside - Lijun Chen; Ning Zhang; Yuqi Huang; Qi Zhang; Yangxin Fang; Jiamin Fu; Yin Yuan; Lu Chen; Xin Chen; Zhenyu Xu; Yifei Li; Hiromi Izawa; et al. (Stem Cell Reviews and Reports, 2023)

Protecting river eco-hydrological processes: insights from water temperature studies - Wenxian Guo; Ning He; Hongxiang Wang; Haitao Zhang; Yicheng Fu (Aquatic Sciences, 2023)

Factors predictive of the biogeographic distribution of comammox Nitrospira in terrestrial ecosystems - Wenlong Gao; Yajun Fu; Changhua Fan; Wen Zhang; Yongsheng Wang; Ning Li; Huiran Liu; Xin Chen; Yuqin Liu; Xiaolong Wu; Qinfen Li; Miao Chen (Soil Biology and Biochemistry, 2023)

An integrated fuzzy AHP and fuzzy TOPSIS approach for screening backfill materials for contaminant containment in slurry trench cutoff walls - Xian-Lei Fu; Hao Ni; Annan Zhou; Zhe-Yuan Jiang; Ning-Jun Jiang; Yan-Jun Du (Journal of Cleaner Production, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Non-uniform thermal characteristics investigation of three-dimensional electrochemical-thermal coupled model for pouch lithium-ion battery - Xiang-Wei Lin; Zhi-Fu Zhou; Xin-Gang Zhu; Bin Chen; Hai Zhu; Ning-Yu Ben; Xu-Dong Wang; Wen-Wei Xu (Journal of Cleaner Production, 2023)

Facilitating photogenerated carrier transfer and water oxidation kinetics of BiVO4 photoanode via novel Zn@Co3C functional layer - Weibing Li; Liming Wang; Jie Zhou; Ning Wang; Xinyang Fu; Yibo Wang; Yuyu Bu; Yaping Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

Conversion and impact of dissolved organic matters in a heterogeneous catalytic peroxymonosulfate system for pollutant degradation - Yanshan Wang; Ning Li; Qinglong Fu; Zhanjun Cheng; Yingjin Song; Beibei Yan; Guanyi Chen; Li'an Hou; Shaobin Wang (Water Research, 2023)

Manure-derived hydrochar superior to manure: Reducing non-point pollution risk by altering nitrogen and phosphorus fugacity in the soil–water system - Yuanyuan Feng; Ning Wang; Haibin Fu; Huifang Xie; Lihong Xue; Yanfang Feng; Gerrard Eddy Jai Poinern; Deli Chen (Waste Management, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Pore density of the benthic foraminiferal test responded to the hypoxia off the Changjiang estuary in the East China Sea - Feifei Wang; Shixiong Yang; Bin Zhai; Shaojun Gong; Junjie Wang; Xiaojin Fu; Jian Yi; Ze Ning (Frontiers in Marine Science, 2023)
The benthic foraminiferal assemblages are commonly used to indicate different oxygenation conditions. In the last few decades, pore characteristics of the benthic foraminiferal tests from the micro-perspective using high-spatial-resolution analysis have been extensively suggested to indicate redox changes. Based on the whole test of the living shallow-infaunal species Bolivina robusta using a more representative and comprehensive method, we observed a significant negative correlation between the pore density (PD) and bottom dissolved oxygen (DO) concentration, and the average PD was about 36% higher in hypoxic environments (DO<3 mg/l) than in oxic environments (DO>3 mg/l). In terms of reproduction pattern in hypoxic environments, the species seemed to mainly choose the asexual life cycle (74.60%) to get more small generations with larger pore size (PS) (asexual 7 μm vs. sexual 4 μm) and exterior ornamentation (irregular papillae) as their survival strategy. The results provide new insight into the benthic foraminiferal ecology to reconstruct the pale-oceanography and paleo-ecology changes in the East China Sea. Moreover, this study has the potential to be applied in broad regions as an independent proxy by comparison to other widely-distributed benthic foraminiferal species.

Organic substitution stimulates ammonia oxidation-driven N2O emissions by distinctively enriching keystone species of ammonia-oxidizing archaea and bacteria in tropical arable soils - Qi Zhang; Miao Chen; Youfeng Leng; Xiaotong Wang; Yajun Fu; Danfeng Wang; Xiongwei Zhao; Wenlong Gao; Ning Li; Xin Chen; Changhua Fan; Qinfen Li (Science of The Total Environment, 2023)

Overlooked impacts of natural organic matter conversion in a Fe(II)-induced peroxymonosulfate activation system for river water remediation - Lan Liang; Guanyi Chen; Jianhui Zhao; Penghui Shao; Ning Li; Mengting He; Qinglong Fu; Beibei Yan; Li-an Hou (Science of The Total Environment, 2023)

Application of automated mineralogy in petroleum geology and development and CO2 sequestration: A review - Changqing Fu; Yi Du; Wenlei Song; Shuxun Sang; Zhejun Pan; Ning Wang (Marine and Petroleum Geology, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Livestock manure-derived hydrochar is more inclined to mitigate soil Global Warming Potential than raw materials based on soil stoichiometry analysis - Yuanyuan Feng; Ning Wang; Huifang Xie; Jing Li; Guanlin Li; Lihong Xue; Haibin Fu; Yanfang Feng; Gerrard Eddy Jai Poinern; Deli Chen (Biology and Fertility of Soils, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Modeling the Operating Performance of a Drinking Water Biological Aerated Filter and the Formation of Organic Nitrogen - Jia Kang; Chu-qiong Song; Ning Zhou; Yao-wen Zhang; Shu-li Liu; Gang-fu Song; Wa-ni Zhou (Environmental Science and Pollution Research, 2023)

Preparation of a g-C3N4/Ag3PO4 composite Z-type photocatalyst and photocatalytic degradation of Ofloxacin: Degradation performance, reaction mechanism, degradation pathway and toxicity evaluation - Renhua Chen; Suying Ding; Ning Fu; Xuechang Ren (Journal of Environmental Chemical Engineering, 2023)

Mechanical deterioration effect and damage evolution characteristics of soft sandstone with different water-immersed heights under uniaxial compression - Han-Dong Liu; Shuai Liu; Hai-Ning Liu; Jia-Xing Chen; Zhi-Guo Xia; Ju-Yun Zhai; Yun-You Fu (Bulletin of Engineering Geology and the Environment, 2023)

Ultrafast extraction of uranium from seawater using photosensitized biohybrid system with bioinspired cascaded strategy - Man Wang; Lijuan Feng; Guangsheng Luo; Tiantian Feng; Shilei Zhao; Hui Wang; Se Shi; Tao Liu; Qiongyao Fu; Jingquan Li; Ning Wang; Yihui Yuan (Journal of Hazardous Materials, 2023)

Secondary pollution of microplastic hetero-aggregates after chlorination: Released contaminants rarely re-adsorbed by the second-formed hetero-aggregates - Yan Jin; Minghui Li; Feiyong Chen; Lin Wang; Lijie Zhang; Zhigang Yang; Ning Wang; Jie Fu; Yang Yu; Xiaoxiang Cheng; Daoji Wu (Journal of Hazardous Materials, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Taphonomic and diagenetic implications of reduction spot formation in Cretaceous red beds from the Jiaolai Basin, Eastern China - Wenzhao Fu; Peter Turner; Thomas Clements; Alan R.T. Spencer; Jifeng Yu; Yu Yang; Bangjie Guo; Zhenguo Ning; Xizhun Zhuo; Michael S. Riley; Jason Hilton (Journal of Asian Earth Sciences, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Antifungal antibodies present in intravenous immunoglobulin derived from China - Yanfang Wang; Yugu Liu; Susu Jiang; Yan Zhao; Jianpiao Cai; Wei Hao; Ning Fu (Brazilian Journal of Microbiology, 2023)
Fungal infections usually occur in immunocompromised patients. Intravenous immunoglobulin (IVIG) has been used as therapeutic interventions for many infectious diseases, but seldom applied in mycosis due to unknown antifungal specificity. This study aims to determine the presence of antifungal antibodies in IVIG. Binding reactivity of IVIG with crude and recombinant antigens of Candida albicans, Aspergillus fumigatus , Cryptococcus neoformans and Talaromyces marneffei were observed in a dose-dependent manner, similar with mixed normal human sera. The antifungal specificity was further confirmed by competitive enzyme-linked immunosorbent assays (ELISA) inhibited by rabbit specific antifungal polyclonal antibodies (PAbs) and homogenous crude antigens with inhibitions of 65.5-87.2% and 73.1-94.2%, respectively. Moreover, IVIG also reacted with fungal glycoproteins (Csa2 , Cpl1 and Mp1p) in a dose-dependent way, which was inhibited by specific rabbit PAbs and homogenous antigens with different inhibitions and pulled down 72.8-83.8% of specific antibodies if preabsorption IVIG with Dynabeads® coupled with homogenous glycoproteins. These results furthermore verified the antifungal specificity of IVIG. Among four brands of IVIG, there was different antifungal IgG against C. albicans ( P < 0.05) and C. neoformans ( P < 0.05), while no difference for A. fumigatus ( P = 0.086) and T. marneffei ( P = 0.057). IVIG contained a significantly higher level of specific IgG for C. albicans than other three fungi ( P <0.001). In conclusion, we proved antifungal IgG against C. albicans , A. fumigatus , C. neoformans and T. marneffei present in IVIG, which might be expected to provide a possible immunoregulation choice for mycosis and an evaluation to humoral immunity against fungi.

Investigation and optimization of methane purification method for natural gas by two-column gas chromatography: A preliminary test for doubly substituted isotopologue (13CH3D) measurements - Tiantian Sun; Jun Cao; Haijun Qiu; Piaoer Fu; Hailong Lu; Zijie Ning; Daohua Chen; Yinan Deng; Shengxiong Yang (Frontiers in Marine Science, 2023)
In this study, optimization of the methane purification method by gas chromatography (GC) is described for the determination of methane clumped isotope compositions of natural gas. Methane was purified under the carrying of helium on the assembly line composed of a vacuum apparatus and two-column gas chromatography. Once methane was detected by the passive thermal conductivity detector (TCD) on the GC, it was collected through a silica trap immersed in liquid nitrogen. Optimum conditions of chromatographic column diameter (1/4 inch outside diameter), temperature (25 °C), and flow rate (50.8 ml min -1 ) have been determined. When N 2 /CH 4 (by volume) is<8.7%, the purification experiment can be undertaken once, while a double purification experiment is required when natural gas samples have an N 2 /CH 4 of 8.7-78.0%. The purification method yielded a purity of 98.4-98.8% with a recovery of 97.3-98.7% on purified methane samples verified by GC determination. N 2 was the main source that contributed to the loss of the purity, however, the N-bearing isobaric interferences ( 14 NH 3 + and 14 NH 4 + ) in purified samples presented<1‰ intensity compared to the methane isotopologues ( 13 CH 4 + and 13 CH 3 D + ), thus we concluded that these interferences have no impact on clumped isotope determinations. The conventional δ 13 C VPDB and δD VSMOW values of purified methane samples were consistent with those of pure methane. A preliminary measurement of Δ 13 CH 3 D (working gas) of purified samples revealed differences of -0.27‰, which was within the internal precision of the measurement. The entire process of a single purification can be completed within two hours. Our proposed method could be used for the clumped isotope purification of natural gas with higher than ~50% methane.

A review on lignin waste valorization by catalytic pyrolysis: Catalyst, reaction system, and industrial symbiosis mode - Shaoqing Wang; Zhen Wan; Yu Han; Yan Jiao; Zhihe Li; Peng Fu; Ning Li; Andong Zhang; Weiming Yi (Journal of Environmental Chemical Engineering, 2023)

Roadside NO2/NOx and primary NO2 from individual vehicles - Peter Brimblecombe; Mengyuan Chu; Chun-Ho Liu; Yunfei Fu; Peng Wei; Zhi Ning (Atmospheric Environment, 2023)

Chronic restraint stress–induced depression-like behavior is mediated by upregulation of melanopsin expression in C57BL/6 mice retina - Yingmei Fu; Shanshan Liu; Yigang Dong; Yixia Gan; Xiaoyun Guo; Hongmei Liu; Qingqing Xu; Ruixue Yuan; Ailing Ning; Wu Hong; Yanmin Peng; Shunying Yu (Psychopharmacology, 2023)

Transmission characteristics, source apportionment and health risk assessment of PM2.5 in a typical industrial city in Northwest China - Kai Xiao; Xiaoqing Yao; Xuechang Ren; Xi Zhang; Ning Fu; Qiuhong Shi (Urban Climate, 2023)

Stochastic analysis on the lateral buckling of a HPHT pipeline considering the spatial variability of seabed - Yu-Min Shi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2023)

Rearranged oleananes in Tertiary oils from the Baiyun Sag, Pearl River Mouth Basin, South China Sea: identification, distribution and geochemical significance - Xiaolin Lu; Meijun Li; Youchuan Li; Yongcai Yang; Ning Wang; Zichao Ran; Ying Fu; Sajjad Ali (Organic Geochemistry, 2023)

Micron SiOx encapsulated into amorphous B, N Co-doped carbon nanotube network for high-capacity and long-durable Li-ion half/full batteries - Bingxin Shen; Ning Fu; Yuwen Chen; Wei Shao; Yurong Yan; Jia Huang; Zhenglong Yang (Chemical Engineering Journal, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

Expression profile of long non-coding RNAs in the intestine of black rockfish Sebastes schlegelii in response to Edwardsiella tarda infection - Xu Yan; Min Cao; Qiang Fu; Ning Yang; Ningning Wang; Lin Song; Chao Li (Journal of Oceanology and Limnology, 2023)

Arylation of indole at C2 catalyzed by palygorskite grafted covalent organic frameworks supported palladium catalyst - Ning Ding; Shang Wu; Qiang Hu; Jutao Liu; Penghui Zhang; Shuaishuai Fu; Huanlei Zhao; Hong Zhang; Fenping Yin; Quanlu Yang (Applied Clay Science, 2023)

Evolution of the mechanical properties of loess in an acidic water environment: mechanism analysis and prediction using a chemical constitutive model - Yao Zhang; Shaoqiang Guo; Zaiqiang Hu; Ning Li; Shaojun Fu; Shuai Shao; Zhijia Xue (Bulletin of Engineering Geology and the Environment, 2022)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Dongxue Li; Yi’na Li; Yiliang Xie; Baoshan Cui; Zhonghua Ning; Shuyan Zhang; Zhenggang Bi; Shouqiang Fu; Chunguang Che (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the contents of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest content in the North Unrestoration, while the TS content appeared highest in the North Restoration. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, the changing trend of soil C/S in the North Unrestoration exhibited a considerably different profile similarity from the North Restoration, which indicates that the ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the high content of soil biogenic elements SOC and high ratio of soil ecological stoichiometry C/N and C/S in the Yellow River Delta induce that they are more sensitive to environmental change. Over the three years, the contributions of soil moisture content, soil salinity, and pH to soil biogenic element contents and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally has a positive effect on the soil biogenic element contents and their ecological stoichiometry in the Yellow River Delta and provides a reference for delta restoration.

Divergent trends of ecosystem‐scale photosynthetic efficiency between arid and humid lands across the globe - Fangli Wei; Shuai Wang; Bojie Fu; Lanhui Wang; Wenmin Zhang; Lixin Wang; Ning Pan; Rasmus Fensholt (Global Ecology and Biogeography, 2022)
Aim Widespread greening and an increasing global terrestrial carbon sink over recent decades have been reported. However, the spatio‐temporal relationships between vegetation greenness and productivity and the factors influencing this relationship remain unclear. We define a new metric of ecosystem‐scale photosynthetic efficiency (EPE) to analyse its spatio‐temporal pattern and investigate how potential drivers regulate the greenness–productivity relationship. Location Global. Time period From 2001 to 2016. Major taxa studied Global terrestrial ecosystems. Methods This study used global datasets of leaf area index (LAI) and solar‐induced fluorescence (SIF) as proxies of vegetation greenness and ecosystem productivity, respectively, to propose a new metric of SIF/LAI, representing ecosystem‐scale photosynthetic efficiency (EPE). We identified the spatial pattern and dynamics of EPE and examined factors influencing EPE. Results The results showed a weaker increase in productivity compared with the global greening rate from 2001 to 2016, suggesting a decline in EPE at the global scale. This decline in EPE indicates a disproportionate increase in terrestrial productivity against the widespread greening. When stratified into areas following an aridity gradient, we found that EPE overall showed upward trends in arid and semi‐arid areas, and downward trends in dry sub‐humid and humid regions. The EPE was controlled primarily by soil moisture, which promoted or constrained the EPE in xeric and mesic ecosystems, respectively. Moreover, the increase in short vegetation cover and atmospheric water demand contributed positively or negatively to EPE changes in xeric and mesic ecosystems, respectively. Main conclusions Our study shows that greening of the Earth is associated with decreasing EPE, revealing that current rates of carbon sequestration do not increase proportionally to greening of the Earth and highlighting that soil moisture is a key controller of EPE. These results help to reduce the uncertainties in future climate change impacts on vegetation dynamics, thus having implications for sustainable ecosystem management and climate change mitigation.

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Establishment of Standard Human Blood Vessel Model Based on Image Registration and Fitting Technology - Dinghao Luo; Junxiang Wu; Ning Wang; Lei Wang; Kai Xie; Songtao Ai; Lingjie Fu; Yongqiang Hao; Wen Wu (Journal of Medical and Biological Engineering, 2022)
Purpose The blood vessel gives key information for pathological changes in a variety of diseases. In view of the crucial role of blood vessel structure, the present study aims to establish a digital human blood vessel standard model for diagnosing blood vessel-related diseases. Methods The present study recruited eight healthy volunteers, and reconstructed their bilateral upper extremity arteries according to CTA. The reconstructed vessels were segmented, registered, and merged into a bunch. After being cut by continuous cut planes, the dispersion of the blood vessel bunches on each cut plane were calculated. Results The results demonstrated that the middle segment of the brachial artery, the proximal segment of the ulnar artery, and the middle and distal segments of the radial artery had a low degree of dispersion. A standard blood vessel model was finally established by the integral method using the low-dispersion segments above. The accuracy of the standard blood vessel model was also verified by an actual contralateral vessel, which revealed that the deviation between the model and the actual normal contralateral brachial artery was relatively small. Conclusion The structure of the model was highly accordant with the real ones, which can be of great help in evaluating the blood vessel changes in blood vessel-related diseases, bone and soft-tissue tumors, and creating accurate surgical plans.

Paleoenvironment controls on organic matter accumulation in transitional shales from the eastern Ordos Basin, China - Jianwei Lv; Songhang Zhang; Ning Yang; Chunbo Fu; Xinlu Yan; Yang Li (Frontiers of Earth Science, 2021)

Effect of nano-CaCO3 on the physical and mechanical properties of analogue to silty mudstone materials - Hong-Yuan Fu; Shuang-Xing Qi; Zhen-Ning Shi; Ling Zeng; Hong-Bin Zhao (Arabian Journal of Geosciences, 2021)

TNIK influence the effects of antipsychotics on Wnt/β-catenin signaling pathway - Ruixue Yuan; Yaojing Li; Yingmei Fu; Ailing Ning; Dongxiang Wang; Ran Zhang; Shunying Yu; Qingqing Xu (Psychopharmacology, 2021)

SUMO conjugating enzyme: a vital player of SUMO pathway in plants - Shantwana Ghimire; Xun Tang; Weigang Liu; Xue Fu; Huanhuan Zhang; Ning Zhang; Huaijun Si (Physiology and Molecular Biology of Plants, 2021)

Dustfall-bound polycyclic aromatic hydrocarbons (PAHs) over the fifth largest Chinese lake: residual levels, source apportionment, and correlations with suspended particulate matter (SPM)-bound PAHs in water - Ning Qin; Xiang-Zhen Kong; Wei He; Qi-Shuang He; Wen-Xiu Liu; Fu-Liu Xu (Environmental Science and Pollution Research, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Impacts of land use change on ecosystem service value in Lijiang River Basin, China - Ning Li; Jinye Wang; Haoyu Wang; Bolin Fu; Jianjun Chen; Wen He (Environmental Science and Pollution Research, 2021)

Geochemical characteristics and its geological application of over-mature Longmaxi shale gas in the northern Guizhou area, China - Yi Zhong; Peng Xia; Shitan Ning; Yong Fu; Qingguang Li; Yin Yu (Arabian Journal of Geosciences, 2021)

Effects of continuous cucumber cropping on crop quality and soil fungal community - Kaining Sun; Longyun Fu; Yang Song; Liang Yuan; Haoran Zhang; Dan Wen; Ning Yang; Xiao Wang; Yaoquan Yue; Xuhua Li; Kean Wang (Environmental Monitoring and Assessment, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Integrated LSM-DFN Modeling of Naturally Fractured Reservoirs: Roughness Effect on Elastic Characteristics - Ning Liu; Yang-Ying Li; Li-Yun Fu; Yue Kong; Wu-Shuang Li (Pure and Applied Geophysics, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Identifying genes for resistant starch, slowly digestible starch, and rapidly digestible starch in rice using genome-wide association studies - Ning Zhang; Maike Wang; Ji Fu; Yi Shen; Yi Ding; Dianxing Wu; Xiaoli Shu; Wenjian Song (Genes & Genomics, 2020)

Patients with radiation enteritis present regulatory T cell impairment associated with CTLA-4 - Xufeng Gong; Genhua Yu; Zongchang Song; Shuqi Huang; Yan Hou; Ning Wang; Wei Zhao; Jingjing Ouyang; Zhengzhou Gu; Haili Hu; Lei Fei; Aixia Fu; et al. (Immunologic Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Presence of organophosphate esters in plasma of patients with hypertension in Hubei Province, China - Yang Li; Dong Li; Jianqiu Chen; Shenghu Zhang; Yourong Fu; Ning Wang; Yanhua Liu; Bin Zhang (Environmental Science and Pollution Research, 2020)

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Development of Nitrogen Fertilizer Topdressing Model for Winter Wheat Based on Critical Nitrogen Dilution Curve - Yang Wang; Youliang Ye; Yufang Huang; Yanan Zhao; Ning Ren; Wen Fu; Songhua Yue (International Journal of Plant Production, 2020)

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

Electron Probe Microanalysis of Monazite and Its Applications to U-Th-Pb Dating of Geological Samples - Wenbin Ning; Junpeng Wang; Deng Xiao; Fenfang Li; Bo Huang; Dong Fu (Journal of Earth Science, 2019)

The Core Role of Bacillus subtilis and Aspergillus fumigatus in Pile-Fermentation Processing of Qingzhuan Brick Tea - Qian Xu; Min Sun; Jingming Ning; Shimao Fang; Ziling Ye; Junhai Chen; Ruiyan Fu (Indian Journal of Microbiology, 2019)

Dynamics of MiRNA Transcriptome in Turbot (Scophthalmus maximus L.) Intestine Following Vibrio anguillarum Infection - Chengbin Gao; Xin Cai; Qiang Fu; Ning Yang; Lin Song; Baofeng Su; Fenghua Tan; Baining Liu; Chao Li (Marine Biotechnology, 2019)

Protective effects of protopanaxatriol on acute liver injury induced by concanavalin A - Lina Jin; Xue Fu; Shuangshuang Yao; Jian Yang; Guang Ning; Zhiguo Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Ethical considerations of cellular immunotherapy for cancer - Sang-sang Ren; Jing-wen Deng; Meng Hong; Yan-li Ren; Hai-jing Fu; Yan-ning Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2019)

A novel method for predicting cadmium concentration in rice grain using genetic algorithm and back-propagation neural network based on soil properties - Yi Xuan Hou; Hua Fu Zhao; Zhuo Zhang; Ke Ning Wu (Environmental Science and Pollution Research, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Characterization of an expressed Triticum monococcum Glu-A1y gene containing a premature termination codon in its C-terminal coding region - G. Chen; M.H. Zhang; X.J. Liu; J.Y. Fu; H.Y. Li; M. Hao; S.Z. Ning; Z.W. Yuan; Z.H. Yan; B.H. Wu; D.C. Liu; L.Q. Zhang (Cereal Research Communications, 2018)

Automatic 40Ar/39Ar Dating Techniques Using Multicollector ARGUS VI Noble Gas Mass Spectrometer with Self-Made Peripheral Apparatus - Xiu-Juan Bai; Hua-Ning Qiu; Wen-Gui Liu; Lian-Fu Mei (Journal of Earth Science, 2018)

Developing China’s National Emission Trading Scheme: Experiences from Existing Global Schemes and China’s Pilot Programs - Bolun Ning; Yongguan Zhu; Zhihong Xu; Bojie Fu (Chinese Geographical Science, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Correlation analysis between the karyotypes and phenotypic traits of Chinese cymbidium cultivars - Huijuan Ning; Suyan Ao; Yirong Fan; Jianxin Fu; Chuanmei Xu (Horticulture, Environment, and Biotechnology, 2018)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Development and trait evaluation of chromosome single-segment substitution lines of O. meridionalis in the background of O. sativa - Ning He; Rouxian Wu; Xiaoping Pan; Liping Peng; Kang Sun; Tuo Zou; Haitao Zhu; Ruizhen Zeng; Ziqiang Liu; Guifu Liu; Shaokui Wang; Guiquan Zhang; et al. (Euphytica, 2017)

Influences of environmental factors on biomass of phytoplankton in the northern part of Tai Lake, China, from 2000 to 2012 - Wenjing Guo; Yuanrong Zhu; Zhiyou Fu; Ning Qin; Hao Wang; Shasha Liu; Yan Hu; Fengchang Wu; John P. Giesy (Environmental Monitoring and Assessment, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Vascular complications following prophylactic balloon occlusion of the internal iliac arteries resolved by successful interventional thrombolysis in a patient with morbidly adherent placenta - Ning Zhang; Wei-hua Lou; Xue-bin Zhang; Jia-ning Fu; Yun-yan Chen; Zhi-guo Zhuang; Jian-hua Lin (Journal of Zhejiang University-SCIENCE B, 2017)

A comprehensive approach from the raw and normalized anomalies to the analysis and prediction of the Beijing extreme rainfall on July 21, 2012 - Ning Jiang; Weihong Qian; Jun Du; Richard H. Grumm; Jiaolan Fu (Natural Hazards, 2016)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Comparative transcriptome analysis of differentially expressed genes between the curly and normal leaves of Cymbidium goeringii var. longibracteatum - Huijuan Ning; Chao Zhang; Jianxin Fu; Yirong Fan (Genes & Genomics, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

Relationships between plant colonization and soil characteristics in the natural recovery of an earthquake-triggered debris flow gully in the Wanglang National Nature Reserve, China - Bo Xu; Jin-niu Wang; Fu-sun Shi; Ning Wu (Journal of Mountain Science, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Characterization of Sclerotinia nivalis causing Sclerotinia rot of Pulsatilla koreana in China - Haijiao Xu; Rujun Zhou; Junfan Fu; Yue Yuan; Hongbo Li; Ning Hao (European Journal of Plant Pathology, 2015)

AtrbohD and AtrbohF negatively regulate lateral root development by changing the localized accumulation of superoxide in primary roots of Arabidopsis - Ning Li; Lirong Sun; Liyue Zhang; Yalin Song; Panpan Hu; Cui Li; Fu Shun Hao (Planta, 2015)

Morphological and molecular identification of powdery mildew of Clematis manshurica caused by Erysiphe aquilegiae in China - Rujun Zhou; Haijiao Xu; Yanghui Ou; Ning Hao; Junfan Fu (Phytoparasitica, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

Effect of different sulfides on cadmium distribution during sludge combustion based on experimental and thermodynamic calculation approaches - Jing-Yong Liu; Jie-Wen Fu; Shui-Yu Sun; Xun-An Ning; Yu-Jie Wang; Tao Chen; Guang-Qian Luo; Wu-Ming Xie; Zuo-Yi Yang; Zhong-Xu Zhuo (Environmental Science and Pollution Research, 2015)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Uptake and recovery of soil nitrogen by bryophytes and vascular plants in an alpine meadow - Jin-niu Wang; Fu-sun Shi; Bo Xu; Qian Wang; Yan Wu; Ning Wu (Journal of Mountain Science, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Organochlorine pesticides in the dust fall around Lake Chaohu, the fifth largest lake in China - Hui-Ling Ouyang; Qing-Mei Wang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (Environmental Monitoring and Assessment, 2014)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Occurrence of rust of Sophora flavescens caused by Uromyces sophorae-flavescentis in China - Ru-Jun Zhou; Jun-Fan Fu; Ning Hao; Zhen Liu; Ying Sun (Phytoparasitica, 2013)

The residual levels and health risks of hexachlorocyclohexanes (HCHs) and dichloro-diphenyl-trichloroethanes (DDTs) in the fish from Lake Baiyangdian, North China - Wen-Jing Wu; Ning Qin; Ying Zhu; Qi-Shuang He; Hui-Ling Ouyang; Wei He; Wen-Xiu Liu; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

An Association Study on Renalase Polymorphisms and Ischemic Stroke in a Chinese Population - Ruyou Zhang; Xiaoying Li; Nana Liu; Xijuan Guo; Wei Liu; Chunping Ning; Zhenzhen Wang; Litao Sun; Songbin Fu (NeuroMolecular Medicine, 2013)

The residues, distribution, and partition of organochlorine pesticides in the water, suspended solids, and sediments from a large Chinese lake (Lake Chaohu) during the high water level period - Wen-Xiu Liu; Wei He; Ning Qin; Xiang-Zhen Kong; Qi-Shuang He; Hui-Ling Ouyang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Water–gas exchange of organochlorine pesticides at Lake Chaohu, a large Chinese lake - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Chen Yang; Yu-Jiao Jiang; Qing-Mei Wang; Bin Yang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Distributions, sources, and ecological risks of hexachlorocyclohexanes in the sediments from Haihe Plain, Northern China - Fu-Liu Xu; Xiang-Zhen Kong; Wei He; Ning Qin; Ying Zhu; Shu Tao (Environmental Science and Pollution Research, 2013)

The polymorphisms of LYRM1 gene and their association with body measurement and ultrasound traits of Qinchuan cattle - Yaokun Li; Jianbin Gao; Ning Yang; Changzhen Fu; Gong Cheng; Hongbao Wang; Linsen Zan (Molecular Biology Reports, 2013)

Distributions, sources, and ecological risks of DDT-related contaminants in water, suspended particulate matter, and sediments from Haihe Plain, Northern China - Yan Wang; Wei He; Ning Qin; Qi-Shuang He; Xiang-Zhen Kong; Shu Tao; Fu-Liu Xu (Environmental Monitoring and Assessment, 2013)

Cell-type-dependent enzymatic hydrolysis of palm residues: chemical and surface characterization of fibers and parenchyma cells - Ning Li; Hao Liu; Shiyu Fu; Shicheng Chen (Biotechnology Letters, 2013)

Residues and ecological risks of organochlorine pesticides in Lake Small Baiyangdian, North China - Yan Wang; Wen-Jing Wu; Wei He; Ning Qin; Qi-Shuang He; Fu-Liu Xu (Environmental Monitoring and Assessment, 2013)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

New perspective of Miocene marine hydrocarbon source rocks in deep-water area in Qiongdongnan Basin of northern South China Sea - Wenhao Li; Zhihuan Zhang; Youchuan Li; Ning Fu (Acta Oceanologica Sinica, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

Na+/H+ Exchanger 1 Gene Expression in Tissues of Yellow Chicken - Zhang-yong Ning; Yu-fu An; Wen-bao Qi; Heng Wang; Jia-qiang Pan; Xin-tao Wu; Ming Liao (Biochemical Genetics, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Inflammatory bowel disease unclassified - Ning Zhou; Wei-xing Chen; Shao-hua Chen; Cheng-fu Xu; You-ming Li (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation and characterization of 40 microsatellite loci for oriental river prawn (Macrobrachium nipponense) and cross-species utility - Hui Qiao; Fajun Li; Hongtuo Fu; Yan Wu; Yongsheng Gong; Sufei Jiang; Yiwei Xiong; Ning Wang (Conservation Genetics Resources, 2011)

Erratum to: Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Twelve novel polymorphic microsatellite loci developed from the Asiatic black bear (Ursus thibetanus) - Hua Wu; Shan-Ning Zhang; Fu-Wen Wei (Conservation Genetics, 2010)

Association between transforming growth factor β1 polymorphisms and left ventricle hypertrophy in essential hypertensive subjects - Hai-Ying Xu; Xu-Wei Hou; Li-Fang Wang; Ning-Fu Wang; Jian Xu (Molecular and Cellular Biochemistry, 2010)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

β-Adrenoceptors, but not dopamine receptors, mediate dopamine-induced ion transport in late distal colon of rats - Xiao-Hui Zhang; Xie-Fu Zhang; Jiu-Qin Zhang; Yue-Min Tian; Hong Xue; Ning Yang; Jin-Xia Zhu (Cell and Tissue Research, 2008)

Benzo[a]pyrene-induced cell cycle progression is through ERKs/cyclin D1 pathway and requires the activation of JNKs and p38 mapk in human diploid lung fibroblasts - Hong Ju Du; Ning Tang; Bing Ci Liu; Bao Rong You; Fu Hai Shen; Meng Ye; Ai Gao; Chuan Shu Huang (Molecular and Cellular Biochemistry, 2006)

Reduced MTA1 Expression by RNAi Inhibits in Vitro Invasion and Migration of Esophageal Squamous Cell Carcinoma Cell Line - Haili Qian; Ning Lu; Liyan Xue; Xiao Liang; Xueyan Zhang; Ming Fu; Yongqiang Xie; Qimin Zhan; Zhihua Liu; Chen Lin (Clinical & Experimental Metastasis, 2005)